Thermal stability and oxidation resistance of Ti–Al–N coatings - Chen, Li (Elsevier Sequoia, 2012)
Ti(1 − x)Al(x)N coatings are widely used for wear resistant applications due to their excellent mechanical and thermal properties, which depend to a great extent on the Al content. Here, we concentrate on a comparative study of the effect of Al content on crystal structure, thermal stability and oxidation resistance of Ti(1 − x)Al(x)N coatings. In agreement to earlier studies, thermal annealing of the individual cubic (c) and wurtzite (w) structured metastable Ti(1 − x)Al(x)N coatings induces decomposition into their stable phases c-TiN and w-AlN. The decomposition process for c-Ti(1 − x)Al(x)N involves an intermediate formation of cubic Al-rich and Ti-rich domains which results in a hardness increase to 34.7 and 34.4 GPa for x = 0.52 and 0.62 when annealed at 950 and 900 °C, respectively. In general, coatings with an Al content closer to the solubility limit, exhibit an earlier decomposition process, and hence an earlier peak-hardness. During exposure of the Ti(1 − x)Al(x)N coatings to ambient air at elevated temperatures Al(2)O(3), TiO(2) and Al(2)TiO(5) are formed. The oxidation resistance of as-deposited single-phase Ti(1 − x)Al(x)N coatings, cubic or wurtzite structured, increases with increasing Al content. However, coatings containing Al contents at the metastable solubility limit, which result in a mixed cubic–wurtzite structure, have the worst oxidation resistance of the Al-containing coatings investigated. The single phase wurtzite structured coating w-Ti(0.25)Al(0.75)N shows the best oxidation resistance, with only ~0.7 μm oxide scale thickness, after thermal exposure for 20 h at 850 °C in ambient air.